The effect of discretionary accruals on firm growth. Empirical evidence for SMEs from emerging Europe - Anton, Sorin Gabriel; Carp, Mihai (Journal of Business Economics and Management, 2020)
The aim of the paper is to assess the effect of discretionary accruals on firm growth while controlling for firm characteristics and macroeconomic environment. Employing a large sample of 1.105 young and high-growth firms (gazelles) from 15 emerging European countries over the period 2006–2014, it has been found that the discretionary accruals negatively influence firm growth. The empirical results suggest that discretionary accruals are used as earnings management tools and this practice is more used over the high-growth period (2006–2009), with negative effects on future performance. Furthermore, the results of the quantile regression employed in the whole period suggest that the earnings management practices have a negative effect on firm growth. The results prove to be robust for different estimation approaches and different sub-samples of gazelles. The findings provide empirical evidence for the need for more detailed information provided by firms on the origin of the accruals, as well as for the use in the performance analysis of some indicators that eliminate the influence of accruals, such as cash flow based ratios.